2019
DOI: 10.3390/educsci10010012
|View full text |Cite
|
Sign up to set email alerts
|

Taking Universal Design Back to Its Roots: Perspectives on Accessibility and Identity in Undergraduate Mathematics

Abstract: Universal Design has been promoted to address the diversity of learners in higher education. However, rarely have Universal Design implementations been evaluated by listening to the voices of disabled students. For this study, we investigated the perceptions of three disabled students who took part in an undergraduate mathematics course designed with the principles of Universal Design for Learning and Assessment. The study consists of two parts. First, we observed the experiences students had in relation to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
(90 reference statements)
0
25
0
2
Order By: Relevance
“…Higher education research has often conceptualised sense of belonging as a basic human need connected to many important factors in students' learning and studying, such as wellbeing and academic performance (Hoffman et al 2002;Theobald et al 2020;Cohen 2007, 2011). Given the previously-reported issues of exclusion in university mathematics context (Adiredja and Andrews-Larson 2017;Croft and Grove 2015;Good et al 2012;Nieminen and Pesonen 2020), it is surprising how rarely the concept of sense of belonging has been directly addressed in this field. The present mixed-methods study identified three student profiles from a sample of university mathematics students based on both their responses to the Mathematical Sense of Belonging instrument (Good et al 2012) and their answers concerning reasons for belonging or not belonging to the mathematics community (as analysed using the framework by Rainey et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher education research has often conceptualised sense of belonging as a basic human need connected to many important factors in students' learning and studying, such as wellbeing and academic performance (Hoffman et al 2002;Theobald et al 2020;Cohen 2007, 2011). Given the previously-reported issues of exclusion in university mathematics context (Adiredja and Andrews-Larson 2017;Croft and Grove 2015;Good et al 2012;Nieminen and Pesonen 2020), it is surprising how rarely the concept of sense of belonging has been directly addressed in this field. The present mixed-methods study identified three student profiles from a sample of university mathematics students based on both their responses to the Mathematical Sense of Belonging instrument (Good et al 2012) and their answers concerning reasons for belonging or not belonging to the mathematics community (as analysed using the framework by Rainey et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This sets an important new viewpoint to future research on active learning environments. Earlier research has underlined that while designing university mathematics learning environments to support underrepresented student groups, it is often not enough to design for them (Nieminen and Pesonen 2020). Therefore, future studies should utilise participatory approaches that let students have their say both in designing and studying learning environments that would support sense of belonging.…”
Section: Limitations Of the Study And Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite legislation that assures equal rights to education for Dutch students in higher education (Researchned 2019), our participants did not always feel they had equal opportunities to participate and so, at times, found themselves outside the boundaries of sense of belonging. For instance, the issue of the students being unable to study in the same learning environments and benefit from the same teaching practices as everyone else becomes a political issue regarding the inaccessibility and the exclusionary discourse it produces (Dolmage 2017;Nieminen 2020;Nieminen and Pesonen 2020;Nieminen 2019). Attention to creating inclusive study environments is needed, and in many countries is mandated by law, although universities may need help to understand the access needs of neurodiverse students.…”
Section: Discussionmentioning
confidence: 99%
“…The self-reflectivity of research communities towards their own political actions through research is especially crucial while working with underrepresented groups such as autistic students. As Nieminen and Pesonen (2020) note, there is a risk to researching and designing learning environments for disabled students, rather than with them; similarly, research can either include or exclude.…”
Section: Discussionmentioning
confidence: 99%